ä½¿ç”¨æ±‰å—åæ—æ•™å¦æé«˜å¦ç”Ÿè®¤è¯†æ±‰å—çš„èƒ½åŠ› - Halimah, .; ., Ina; ., Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
æ‘˜è¦ï¼šæœ¬æ–‡çš„ä¸»è¦ç›®çš„æ˜¯äº†è§£æ±‰å—åæ—æ•™å¦å¯¹å¦ç”Ÿå¦ä¹ æ±‰å—çš„æ•ˆæžœï¼Œæ˜¯å¦æœ‰æ•ˆï¼Œæé«˜å¦ç”Ÿè®¤è¯†æ±‰å—çš„èƒ½åŠ›ã€‚ç ”ç©¶å¯¹è±¡æ˜¯å¤ç”¸å›½ç«‹ç¬¬ä¸‰ä¸å¦ç†ç§‘ä¸€çå’Œ ç†ç§‘äºŒçä¸‰å¹´çº§çš„å¦ç”Ÿï¼Œå…±æœ‰70åå¦ç”Ÿï¼ˆç”·ç”Ÿ22åï¼›å¥³ç”Ÿ48åï¼‰ã€‚ç ”ç©¶æ–¹æ³•æ˜¯æµ‹è¯•æ³•ã€å®žéªŒæ³•å’Œç»Ÿè®¡æ³•ã€‚æ ¹æ®æœ¬æ–‡çš„æ•™å¦å®žéªŒä»¥åŠå‰åŽæµ‹çš„ç»Ÿè®¡ä¸Žåˆ†æžï¼Œç¬”è€…äº†è§£åˆ°ï¼Œé€šè¿‡äº†æ±‰å—åæ—æ•™å¦åŽï¼Œå¦ç”Ÿå¯¹æ±‰å—çš„æ£ç¡®çŽ‡æ˜Žæ˜¾æé«˜äº†ï¼Œå¦ç”Ÿå¯¹æ±‰å—çš„æŽŒæ¡èƒ½åŠ›å¤§éƒ¨åˆ†éƒ½å·²ç»è¾¾åˆ°90%ä»¥ä¸Šã€‚è¿™è¡¨ç¤ºæ±‰å—åæ—æ•™å¦å¾ˆæœ‰æ•ˆï¼Œä¼šå¸®åŠ©å¦ç”Ÿæ›´å®¹æ˜“è®¤è¯†æ±‰å—ä¸Žä¼šæé«˜å¦ç”Ÿçš„è®¤è¯†æ±‰å—çš„èƒ½åŠ›ã€‚ä»Žè€Œå–å¾—æ›´å¥½çš„æ•™å¦æ•ˆæžœã€‚ å…³é”®è¯ï¼šæ±‰å—ï¼›æ±‰å—æ•™å¦ï¼›æ±‰å—åæ—æ•™å¦ Abstract : The purpose of this research is to know the effect of Chinese character component teaching method for the student to learn Chinese characters, to know that if it can increase the student ability in understanding Chinese characters. The object of this research are students of the third grade National Senior High Schoolâ€™s 3, science class one and science class two, with total students were 70 students (22 male; 48 female). The research method are aÂ  method of test, practice and count method. Based on analysis of the teaching learning process in the classroom and the result in pre-test and post-test, the writer gots the result after used the Chinese character component teaching method that studets test scores increased until 90%. It shows that the using of Chinese charcter component teaching methode improve the studentâ€™s abilitity in understanding Chinese characters effectively. In conclusion, it gives a good effect in studentâ€™s learning. Key words: Chinese characters; Chinese character teaching method; Chinese character component teaching method